Perbandingan Antara Perspektif Barat dan Islam Mengenai Konsep Narsistik dan Ujub - Nora Nurhadhani (Jurnal Psikologi Terapan, 2018)
The purpose of this journal is to analyze the similarities and differences between the terms narcissistic in the study of western psychology and ujub in the perspective of Islam. In western psychology there are views or theories about narcissistic. Narcissistic is an exaggerated admiration and awe of self, and an extreme need for the attention and worship of others against him. This has a resemblance to ujub according to Islamic perspective, where ujub is an exaggerated assumption or self-esteem, assuming that he has many good deeds and possesses more gifts than others and forgets his creator. Although there are some semblance of narcissistic and ujub, on the other side there are also differences of views according to their respective flow about both concepts.